Open-Door Cervical Laminoplasty with Preservation of Posterior Structures - Abdullah, Kalil G. (Thieme Medical Publishers, 2012)
Objective To demonstrate that preservation of all posterior structures during open-door laminoplasty (ODL) is associated with a significant preservation of motion. Methods Fifteen patients underwent cervical ODL by one surgeon for treatment of cervical spondylotic myelopathy. An open-door technique was employed, and the laminae on the open side were reconstructed using miniplates with allograft strut bone graft. All spinous processes and interspinous and supraspinous ligaments were preserved within the operative levels and between supra- and subjacent levels in all patients. Postoperative radiographs were obtained 1.5, 3, 6, and 12 months. Computed tomography scans were obtained at 12 months. Results There were no significant intraoperative or perioperative complications. Postoperatively, the neutral angle was 6.8 ± 11.5 degrees (95% confidence interval: 0.5 to 13.1), representing a loss of lordosis of 3 degrees (not significant). The difference between the preoperative and postoperative arc range of motion was 5.96 ± 11.9 degrees (confidence interval: −0.62 to 12.5). The average percent loss of motion was 3.5% ± (0.1 to 6.9%). Four patients had an increased range of motion postoperatively. Conclusion Open-door laminoplasty with preservation of all posterior structures provides greater preservation of motion than has been previously described.